Effects of Ecosystem Balance Simulation Games within a Problem-Based Learning Model on High School Students’ Critical Thinking Skills - Dani Ramdani; Purwati Kuswarini; Liah Badriah; Sukma Jaya Asmara (Journal of General Education and Humanities, 2026)
This study aims to evaluate the effectiveness of integrating the Problem-Based Learning (PBL) model with an ecosystem balance simulation game in enhancing senior high school students’ critical thinking skills. A quasi-experimental method with a matching-only posttest-only control group design was employed, involving 90 purposively selected students divided into three groups. The critical thinking instrument consisted of 12 validated essay items. Data analysis included the Kolmogorov–Smirnov normality test, Levene’s homogeneity test, and ANOVA followed by the LSD post hoc test. The results indicate a significant difference among the groups (Sig. = 0.019), with post hoc analysis showing that the experimental group performed significantly better than the conventional group, but did not differ significantly from the PBL-only group. These findings suggest that integrating simulation games into the PBL framework is associated with improved critical thinking outcomes compared to conventional instruction, while yielding results comparable to PBL without simulation support. This indicates that simulation-based PBL may serve as a complementary instructional approach that supports student engagement and conceptual understanding. The study’s implications highlight the importance of integrating interactive digital media in ecology instruction to support the development of students’ 21st-century competencies.